Therapeutic role of immunomodulators during the COVID-19 pandemic– a narrative review. Issue 2 (17th February 2022) - Al-Hajeri, Hebah; Baroun, Fatemah; Abutiban, Fatemah; Al-Mutairi, Muna; Ali, Yasser; Alawadhi, Adel; Albasri, Anwar; Aldei, Ali; AlEnizi, Ahmad; Alhadhood, Naser; Al-Herz, Adeeba; Alkadi, Amjad; et al.
ABSTRACT: The emergency state caused by COVID-19 saw the use of immunomodulators despite the absence of robust research. To date, the results of relatively few randomized controlled trials have been published, and methodological approaches are riddled with bias and heterogeneity. Anti-SARS-CoV-2 antibodies, convalescent plasma and the JAK inhibitor baricitinib have gained Emergency Use Authorizations and tentative recommendations for their use in clinical practice alone or in combination with other therapies. Anti-SARS-CoV-2 antibodies are predominating the management of non-hospitalized patients, while the inpatient setting is seeing the use of convalescent plasma, baricitinib, tofacitinib, tocilizumab, sarilumab, and corticosteroids, as applicable. Available clinical data also suggest the potential clinical benefit of the early administration of blood-derived products (e.g. convalescent plasma, non-SARS-CoV-2-specific immunoglobins) and the blockade of factors implicated in the hyperinflammatory state of severe COVID-19 (Interleukin 1 and 6; Janus Kinase). Immune therapies seem to have a protective effect and using immunomodulators alone or in combination with viral replication inhibitors and other treatment modalities might prevent progression into severe COVID-19 disease, cytokine storm and death. Future trials should address existing gaps and reshape the landscape of COVID-19 management.